Numerical Modelling and Proposed Design Rules of 7075-T6 and AA-6086 High-Strength Aluminium Alloy Channels under Concentrated Loading - Jianhang Fu; Gang Sun; Xiaoyong Sun (Buildings, 2023)
This study presents a detailed numerical investigation into the web buckling behaviour exhibited by high-strength aluminium alloy channels, namely 7075-T6 and AA-6086, when subjected to concentrated loading. A nonlinear finite element (FE) model was established and verified using the experimental data reported by other researchers, and the material properties of 7075-T6 and AA-6086 high-strength aluminium alloy were obtained through the literature. A parametric study comprising 1024 models was performed using the validated FE models. Variables examined in this work included web slenderness ratio, internal corner radii, bearing lengths, and aluminium alloy grades. The numerical results generated by the parametric investigation were used to evaluate the applicability and reliability of the most recent design specifications given in the Australian and New Zealand Standards (AS/NZ S4600) (2018) and Australian Standards (AS/NZS 1664.1) (1997). The comparison indicated that the calculated design strength using AS/NZ S4600 was over-conservative by 41% and 43% for 7075-T6 and AA-6086 aluminium alloy, correspondingly, while the design strength computed using AS/NZS 1664.1 was marginally unconservative, compared to numerical results. Finally, using bivariate linear regression analysis, new design formulas with new coefficients for determining the web buckling behaviour of 7075-T6 and AA-6086 high-strength aluminium alloy channels were proposed. A reliability analysis was then undertaken, indicating that the proposed design equations possess the capability of accurately predicting the web buckling behaviour of these members.